Kinetics study of heterogeneous continuous-flow nitration of trifluoromethoxybenzene. Issue 3 (2nd May 2018) - Wen, Zhenghui; Yang, Mei; Zhao, Shuainan; Zhou, Feng; Chen, Guangwen
Abstract : Trifluoromethoxybenzene (TFMB) nitration was studied in a microreactor, furnishing kinetic data that promoted the process development of large-scale synthesis. Abstract : The kinetics and mass transfer characteristics of the nitration of trifluoromethoxybenzene (TFMB) with a mixed acid were investigated in microchannel reactors. By assuming the intrinsic reaction as the rate-determining step, a quasi-homogeneous reaction kinetic model was proposed and utilized to calculate the observed rate constant. The intrinsic reaction rate constant was then calculated by virtue of an activity coefficient function, M c function. To identify the heterogeneous reaction regime, the Hatta number was obtained, which was in the range of 0.018 to 0.081. The low value of the Hatta number justified the previous assumption. Moreover, the proposed model was utilized to predict the product yields in the microchannel reactor, which are also in great agreement with the experimental results.